2017
DOI: 10.21595/jve.2017.18263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of asymmetric structure parameters on rolling mill stability

Abstract: Considering the asymmetric structure of a rolling mill system, a chatter model is established by coupling a rolling process model and structure model to describe the asymmetric vibration characteristics. According to this mathematical model, the critical rolling speed is determined by calculating eigenvalues of the characteristic matrix. Model correctness and validity are confirmed by an experimental observation of a 2030 cold rolling mill. On this basis, the effects of asymmetric structure parameters on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Especially for vertical vibration, a large amount of energy will be accumulated in a short time, which can lead to thickness fluctuations of the strip as well as the stripes on the surface of the rolled steel products, and even cause the damage of the equipment. To avoid the adverse effects caused by the vibration, the emergency method for the rolling mill vibration control is to slow the rolling speed down [8], [9]. However, the reduction of rolling speed affects the production efficiency and can not fundamentally solve the problem of rolling mill vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for vertical vibration, a large amount of energy will be accumulated in a short time, which can lead to thickness fluctuations of the strip as well as the stripes on the surface of the rolled steel products, and even cause the damage of the equipment. To avoid the adverse effects caused by the vibration, the emergency method for the rolling mill vibration control is to slow the rolling speed down [8], [9]. However, the reduction of rolling speed affects the production efficiency and can not fundamentally solve the problem of rolling mill vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the asymmetric structure of the rolling mill system, Huang [19] established a chatter model by coupling a rolling process model and structure model to describe the asymmetric vibration characteristics, and found that the influence of the asymmetric structure parameters on the stability and critical conditions is noteworthy. In [20], Ma et al established a structural optimization method for a new Y-type rolling mill, which can solve the multiobjective problem of more complex constraints in engineering.…”
Section: Introductionmentioning
confidence: 99%